EVALUASI PROGRAM PENGEMBANGAN KAWASAN AGROPOLITAN â€œPAKAKAANâ€ DI TOMPASO INDUK KABUPATEN MINAHASA - Falentino Bryan Kolibu; Noortje Marselianie Benu; Sherly Gladys Jocom (Sam Ratulangi University, 2021)
The purpose of this research is to evaluate the Agropolitan Area Development program PAKAKAAN in Tompaso Subdistrict. The research was conducted in November 2020 - January 2021. The data used in this study are primary and secondary data. The primary data was obtained through an interview with the head of BPP (Agricultural Counseling Center). Secondary data was obtained from agencies related to this research. The results of this research can be seen that the Tompaso area has the potential as an agropolitan area development. Tompaso region itself is included in the development of PAKAKAAN agropolitan area in Minahasa district. The development of Pakakaan Agropolitan Area in Tompaso area can be seen from the majority of the population in the Tompaso region as farmers, supported by the most production center facilities that can be developed, rice fields. But based on the survey in the Tompaso area there is still much that needs to be improved and there needs to be a capital support facility for farmers or the community.